Terapi Komplementari terhadap Penurunan Nyeri pada Pasien Kanker - Novita Sari; Dewi Elizadiani Suza; Mula Tarigan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to identify and evaluate the effect of intervention in reducing pain in cancer patients. The method used is a systematic review through the EBSCO, PubMed and ProQuest databases. The articles selected the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) diagram method. The results showed that complementary interventions such as Aromatherapy Massage, Reflexology, Acupuncture, Hypnotherapy, Acupressure, Healing Touch and Massage showed significant results in reducing pain in cancer patients. In conclusion, complementary interventions can help reduce pain in cancer patients. Keywords: Cancer Pain, Complementary Therapy